Is China the future market of Adidas - Ivanovic, Dunja (2020)
In the following report a certain issue which could have an impact on Adidas’ valuation outcome and which I recognized while doing the Equity research is briefly addressed. The aim of the report is to understand whether China is really the future market of Adidas and if Adidas’ market share in this market could continue to grow at double-digit rates projected in the main report. In the first part of the report a short overview of Chinese sportswear industry and its trends is given. In the next step, a detailed SWOT analysis of Adidas position in China was conducted in order to better understand possible future scenarios. After identifying the main strengths, weaknesses, opportunities and threats, I presented a scenario analysis with 3 cases: base case, best case, worst case. Based on the outcome of the scenario analysis, and obtained share prices, I concluded that Adidas may be undervalued by the market as the share price calculated in all 3 scenarios was higher than the Adidas’ current share price of EUR273